Oxidative modifications of the Photosystem II D1 protein by reactive oxygen species: from isolated protein to cyanobacterial cells - Lupínková, Lenka; Komenda, Josef (Photochemistry and photobiology, 2004)
Action of reactive oxygen species (ROS) on the isolated D1 protein, a key component of Photosystem II (PSII) complex, was studied and compared with the effect of high irradiance on this protein in mildly solubilized photosynthetic membranes and cells of the cyanobacterium Synechocystis. Whereas singlet oxygen caused mainly protein modification reflected by shift of its electrophoretic mobility, action of hydrogen peroxide and superoxide resulted in generation of specific fragments. Hydroxyl radicals as the most ROS induced fast disappearance of the protein. The results substantiate the ability of ROS to cause direct scission of the D1 peptide bonds. Similar D1 modification, fragmentation and additionally cross-linking with other PSII subunits were observed during illumination or hydrogen peroxide treatment of mildly solubilized thylakoids. Peroxide-induced fragmentation did not occur in thylakoids of the strain lacking a ligand to the nonheme iron, confirming the role of this prosthetic group in the D1-specific cleavage. The D1 modification, fragmentation and cross-linking were suppressed by ROS scavengers, supporting the direct role of ROS in these phenomena. Identical symptoms of the ROS-induced D1 damage were detected in illuminated cells of Synechocystis mutants with a higher probability of ROS formation, documenting the relevance of the in vitro results for the situation in vivo.
Keywords: Molecular Sequence Data; sekvence aminokyselin; ligandy; fotosystém II (proteinový komplex); sinice; Light; reaktivní formy kyslíku; Photosystem II Protein Complex; Thylakoids; Cyanobacteria; světlo; mutace; peroxid vodíku; železo; superoxidy; Oxidation-Reduction; hem; Peptide Fragments; Reactive Oxygen Species; Iron; Ligands; Mutation; Amino Acid Sequence; peptidové fragmenty; sbalování proteinů; Superoxides; oxidace-redukce; molekulární sekvence - údaje; tylakoidy; Hydrogen Peroxide; Protein Folding; Heme